Glimpses of the colonial collections at the 1862 London Exhibition: The case of the Angolan ‘Objects’ at the Portuguese section - Albuquerque, Sara (2022)
The 1862 London Exhibition ‘was a symbol of mid-Victorian aspiration’ with a clear image to the world of Britain’s ambition and its empire. These kind of exhibitions were opportunities for other empires, such as the Portuguese empire to assert and highlight the potential of its colonies. The case of the Portuguese representation during the 19th century in world exhibitions has been examined, however, the display of colonial products remains somehow less explored. This research examines the representation of Portugal and its colonies at the 1862 London Exhibition, in particular the case of the colonial objects of natural history collected what today is known as Angola. Several aspects of the exhibition were analysed, in particular: objects, spaces and actors involved in the preparation of the Portuguese section. Regarding the later, two main figures were crucial for the organisation of this representation: Friedrich Welwitsch (1806-1872) organised, contributed and suggested objects that should be collected from Angola and Júlio Máximo de Oliveira Pimentel (the viscount of Vila Maior, 1809-1884) the royal commissioner at the London Exhibition. In order to understand which objects were on display, Welwitsch’s publications: Explanatory Synopsis of Samples of Timber and Medicinal Drugs (1862) and The Preliminary Notes on various objects from Angola (1861) were crucial to this research. Although the Portuguese representation was severely criticised by the press, Welwitsch was awarded with four gold medals for the colonial objects presented.